Incompatible Crossmatch with Bombay Phenotype (Oh) - A Case Report (Pulse, 2017)
Blood serology plays a vital role in transfusion medicine. Presence of an irregular antibody (anti H) in the plasma reacting with all the red cells exhibiting the normal red cell ABO phenotype, the h/h (Bombay) phenotype. The h/h phenotype also known as Oh or Bombay blood group is a rare blood type. It was first discovered in Bombay (Mumbai) in India by Dr.Y.G. Bhende et al in 19521 Generally present in about 4 per million of the human population, though in some places such as Mumbai (Bombay) locals can have occurrences in as much as 1 in 10,000 of inhabitants2 It is also very rare in Bangladesh. The first case was reported in 1990 where three sisters in a same family were of 'Bombay' phenotype3. A 28-year-old male of Noakhali district was admitted to Apollo Hospitals Dhaka on 21st may 2016 with road traffic accident with pelvic fracture. His ABC and Rh blood group was detected as 0 positive by usual blood grouping test procedure. But his cross match was incompatible with several 0 positive blood units. Though the patients blood group phenotype initially mimic normal group 0 type by usual test procedure but became apparent when his serum was tested against group 0 red cells and strong Mediate spin agglutination developed at a thermal range 4° to 37°C. After testing with anti H Lectin, Ulex europaeus having anti H like activity, it was detected as Bombay blood group. Therefore, proper serum grouping using A cell, B cell and 0 cell is necessary to detect this group. Bombay phenotype individual do not express H, A and B antigen on their red cells and secretions but their plasma contains potent anti H, anti A and anti B due to lack H antigen4 Normal 0 group red cells does not have A or B antigen but their membrane expresses abundant H antigen. Anti H of Bombay phenotype serum gives incompatible cross match with all red blood cells of normal ABO phenotype containing H antigen. oh phenotype person can receive only autologous blood or blood from another Bombay blood group donor.5 This patient has received blood from her own sister who was also Bombay phenotype but his other four brothers were normal 0 group. Later on he was transfused with blood from Bombay blood group donor, arranged from Think Foundation, Mumbai, India for his orthopedic surgery. Both forward and reverse grouping is important for safe transfusion. If not followed, it may lead to people with Bombay blood group, not being detected and categorized as 0 group. Therefore, proper reverse grouping is necessary to detect this group and cross matching at different thermal range also plays a vital role in transfusion safety.Pulse Vol.9 January-December 2016 p.54-59